2015
DOI: 10.4137/jen.s22512
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and Physiological Factors of Neuroprotection in Hypoxia-tolerant Models: Pharmacological Clues for the Treatment of Stroke

Abstract: The naked mole-rat possesses several unique physiological and molecular features that underlie their remarkably and exceptional resistance to tissue hypoxia. Elevated pattern of Epo, an erythropoietin (Epo) factor; c-fos; vascular endothelial growth factor (VEGF); and hypoxia-inducible factors (HIF-1α) contribute to the adaptive strategy to cope with hypoxic stress. Moreover, the naked mole-rat has a lower metabolic rate than any other eutherian mammal of comparable size that has been studied. The ability to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…McNab () was the first to suggest that subterranean rodents live under constant hypoxia and hypercapnia. Physiological adaptations of burrowing mammals to the subterrestrial microclimate, especially mechanisms allowing them to cope with severe hypoxia and hypercapnia, have been studied (Larson, Drew, Folkow, Milton, & Park, ; Larson & Park, ; Nathaniel, Soyinka, Adedeji, & Imeh‐Nathaniel, ; Park et al., ; Schmidt, Hangmann, Shams, Avivi, & Hankeln, ; Shams, Avivi, & Nevo, ). However, evidence accumulates that subterranean mammals, including African mole‐rats, Middle East mole‐rats and North American moles, as well as theoretical models, do not necessarily live in constant hypoxic and hypercapnic microenvironments (Roper, Bennett, Conradt, & Molteno, ; Schaefer & Sadleir, ; Shams, Nevo, & Avivi, ; Withers, ).…”
Section: Introductionmentioning
confidence: 99%
“…McNab () was the first to suggest that subterranean rodents live under constant hypoxia and hypercapnia. Physiological adaptations of burrowing mammals to the subterrestrial microclimate, especially mechanisms allowing them to cope with severe hypoxia and hypercapnia, have been studied (Larson, Drew, Folkow, Milton, & Park, ; Larson & Park, ; Nathaniel, Soyinka, Adedeji, & Imeh‐Nathaniel, ; Park et al., ; Schmidt, Hangmann, Shams, Avivi, & Hankeln, ; Shams, Avivi, & Nevo, ). However, evidence accumulates that subterranean mammals, including African mole‐rats, Middle East mole‐rats and North American moles, as well as theoretical models, do not necessarily live in constant hypoxic and hypercapnic microenvironments (Roper, Bennett, Conradt, & Molteno, ; Schaefer & Sadleir, ; Shams, Nevo, & Avivi, ; Withers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, or low oxygen tension, is a unique environmental stress that not only represents the insufficient oxygen supply to cells and tissues but also occurs during a range of physiologic and pathophysiological circumstances, including development, inflammation, tissue ischemia, and tumor growth (1)(2)(3). Aerobic organisms and cells have developed complex adaptive mechanisms to maintain oxygen homeostasis and evolved physiologic and biochemical responses to survive hypoxic stress (4)(5)(6). Two well-studied O 2 -sensitive signaling pathways are implicated in promoting hypoxia tolerance: signaling through mTOR (mammalian target of rapamycin) that regulates mRNA translation initiation and signaling through activation of the unfolded protein response that alleviates endoplasmic reticulum stress (3,7).…”
mentioning
confidence: 99%
“…Previous studies suggested that delivering the desired genes into the cells may overcome some limitations of cells and facilitate therapeutic efficiency after cell transplantation [9,10]. Hypoxia inducible factor-1 alpha (HIF-1a) is one of the most important regulators in response to oxygen levels, and the stabilization of HIF-1a in cells may promote activation and migration [11][12][13].…”
Section: Introductionmentioning
confidence: 99%